2014
DOI: 10.17569/tojqi.77912
|View full text |Cite
|
Sign up to set email alerts
|

The Portrait of a Good Foreign Language Teacher: A Cross-Interview Analysis of Private Language Course Administrators’ Opinions

Abstract: The attempt to present the profile of a good language teacher is an early arrival, dating back to 1920s. The literature to date abounds with much scholarly attention to exploration of mainly students' and teachers' point of view regarding the issue. However, the paucity of research into other different perspectives in Turkey serves as the backcloth of the current study qualitative in nature, which employs in-depth interviews with the six administrators of six private courses in a province in the northeast part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
3
6
1
Order By: Relevance
“…The findings of the current study in respect to teacher's authority are in line with the studies conducted both in Turkey and abroad (Kourieos & Evripidou 2013;Erbay et al 2014). However, the high frequency of "teacher's authority" in the present study contradicts the lower frequency of "teacher's authority" in the study by Arikan et al (2008) which was also conducted in the Turkish educational context.…”
Section: Teacher As the Authoritysupporting
confidence: 89%
See 4 more Smart Citations
“…The findings of the current study in respect to teacher's authority are in line with the studies conducted both in Turkey and abroad (Kourieos & Evripidou 2013;Erbay et al 2014). However, the high frequency of "teacher's authority" in the present study contradicts the lower frequency of "teacher's authority" in the study by Arikan et al (2008) which was also conducted in the Turkish educational context.…”
Section: Teacher As the Authoritysupporting
confidence: 89%
“…The findings of the present study pertaining to being knowledgeable about the target culture as one of the important qualities of an effective language teacher are in line with the studies by Borg (2006), Arıkan et al (2008), Kourieos &Evripidou (2013), andErbayet al (2014) which concluded that the teacher's knowledge of the target culture was one of the important attributes of an effective language teacher. However, it might be noteworthy to mention that the present study differs from the related studies in that the item "being knowledgeable on target culture" had a higher frequency, as compared to the frequencies for the same item in the other studies by Arıkan et al (2008), Kourieos & Evripidou (2013), and Erbay et al (2014).…”
Section: Knows About the Target Culturecontrasting
confidence: 88%
See 3 more Smart Citations